2020
DOI: 10.3390/polym12061384
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Eco-Friendly Materials Based on Poly(3-hydroxybutyrate) (PHB) and TiO2 with Antifungal Activity Prospective for Esca Treatment

Abstract: Esca is a type of grapevine trunk disease that severely affects vine yield and longevity. Phaeomoniella chlamydospora (P. chlamydospora) is one of the main fungi associated with esca. The aim of the present study was to obtain eco-friendly materials with potential antifungal activity against P. chlamydospora based on biodegradable and biocompatible poly(3-hydroxybutyrate) (PHB), nanosized TiO2-anatase (nanoTiO2), and chitosan oligomers (COS) by conjunction of electrospinning and electrospraying. One-pot electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…As expected, the addition of TiO 2 led to the increase in contact angles to 116.7 • ± 3.75 • and 122.6 • ± 4.24 • for PMMA/5TiO 2 and PMMA/10TiO 2 , respectively. These results were in accordance with our previous findings and with the literature data [25,26]. Therefore, before UV irradiation the contact angles were in the hydrophobic region (above 90 • ), which is due to the hydrophobic surface of the PMMA fibers.…”
Section: Pmma/tio 2 Composites Fabrication and Characterizationsupporting
confidence: 93%
“…As expected, the addition of TiO 2 led to the increase in contact angles to 116.7 • ± 3.75 • and 122.6 • ± 4.24 • for PMMA/5TiO 2 and PMMA/10TiO 2 , respectively. These results were in accordance with our previous findings and with the literature data [25,26]. Therefore, before UV irradiation the contact angles were in the hydrophobic region (above 90 • ), which is due to the hydrophobic surface of the PMMA fibers.…”
Section: Pmma/tio 2 Composites Fabrication and Characterizationsupporting
confidence: 93%
“…The authors reported, however, that more effective polymers and antifungal agents should be used. Some authors have also proposed an original approach and have successfully obtained fibrous materials from poly(3-hydroxybutyrate), nanosized TiO 2 -anatase, and chitosan oligomers (COS) with antifungal activity for plant protection via a combination of electrospinning and electrospraying [16]. The obtained eco-friendly materials possess high roughness, hydrophobicity, and antifungal activity against P. chlamydospora.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous materials based on PHB, nanosized TiO 2 —anatase and chitosan oligomers—have also been successfully obtained by simultaneous electrospinning and electrospraying [ 108 ]. One-pot electrospinning of a dispersion of nanosized TiO 2 nanoparticles in PHB solution resulted in obtaining of materials with design type “in”, in which TiO 2 was incorporated in the fibers.…”
Section: Electrospun Fibrous Materials With Antifungal Activity Again...mentioning
confidence: 99%